SEMIOTIC ANALYSIS LACK OF NEED BY LOOSING FATHER IN PARLE A MON PERE BY CELINE DION - imelda Malawaty Simorangkir; Yulia Sofiani Zaimar; Yosi Maeleona Passandaran (FKIP, Universitas Banten Jaya, 2022)
Language is the most important media for human’s communication. By using language, human can interact, socialize, and cooperate with others, because in essence language is a means of communication. Given the importance of language as a means of communication, in the process of conveying information to others it must be clear and easy to understand, like in literary works. Literary works can also consider as a part of communication. In every literary works, including in song lyric would contain a massage. Lyric songs usually contain experiences and ideas of the authors who are summarized in a particular theme, parsed and conveyed to listeners through language. Song lyrics are an expression of the author's feelings, thoughts and ideas which are realized in a special language. In this research, the researcher would like to research Parle A Mon Pere song, by Celine Dion. This research uses Roland Barthes' semiotic theory, which is collaborated with Jaques Lacan's psychoanalysis theory. Meanwhile, Barthes' myth theory is used to examine the hidden meanings which the songwriters want to convey. This research uses descriptive qualitative method. The researcher would carefully note data in the form of words, sentences and speech. The choice of content analysis techniques is analyzing words. The content analysis techniques are used to understand messages, seen as unstructured data. The result of this research is that researchers can find hidden meanings, that a girl will feel empty if she loses her father. This is obtained through the translation of the signifier and the signified, which is obtained from the sentence in the song Parle A Mon Pere, by Celine Dion.